Atmospheric deposition and land-surface runoff driven nutrient flushing in Ganga River (India). Issue 1 (1st January 2020) - Pandey, Jitendra; Pandey, Usha; Singh, Anand V.; Jaiswal, Deepa; Siddiqui, Ekabal; Verma, Kavita
ABSTRACT: Disproportionate addition of nutrients can alter the nutrient stoichiometric balance of surface water bodies. In the present study, we investigated the atmospheric deposition (AD) and runoff-induced nutrient enrichment and N:P stoichiometric shifts in the Ganga River along a 35 km stretch of Varanasi city. The region receives 8–42 kg ha −1 of reactive-N (NO3 − + NH4 + ) and 0.40–3.10 kg ha −1 of PO4 3- through AD annually. The most polluted Rajghat Site receives 770.50 tons of reactive-N (Nr) and 64.50 tons of PO4 3- annually as AD input in the sub-watershed; and 25.10 tons of Nr and 2.09 tons of PO4 3- directly on the water surface. Concentrations of nutrients in surface runoff increased with AD input irrespective of land use. Among land use categories, the runoff nitrate was highest from agricultural catchment while NH4 + and PO4 3- were highest from urban areas. The study showed that the AD-runoff coupled with additional supplies could substantially alter the overall load and stoichiometric ratios of critical nutrients with a consequent effect on ecological functioning of the river in long-run.